Past, present and future of historical information science - Boonstra, Onno (DANS, 2006)
This book evaluates the results of two decades of research in 'history and computing'. In spite of the fact that a lot has been accomplished, the report indicates critical places for improvement. Many historians and other humanities scholars seem satisfied with standard office tools, which do not always suit their complex sources and research questions. While more and more archival sources have become available in digital form, there has not been enough attention to the development of computational methods to process and analyse them. As a result, the level of technical sophistication in many historical studies has remained rather low. The authors propose a new research agenda and provide requirements for an adequate research infrastructure for future historical information science.